Cardiovascular Diseases among Suiciders: A Population-Based Study in Northern Finland Population - Mainio, Arja (Hindawi Publishing Corporation, 2010)
Objective. Depression has been found to be an independent risk factor with cardiovascular diseases (CVDs) and also associated with increased mortality among these patients. Method. We used a comprehensive database of all suicides (n = 2, 283) committed in Northern Finland with information on all hospital-treated cardiovascular diseases and psychiatric disorders. Results. Coronary artery disease (CAD) had been present in 7.7% and other cardiovascular diseases (CVDs) in 11.6% of the suiciders. The likelihood of suicide for patients with hospital-treated CAD was estimated to be two-fold compared to the general population while likelihood for suicide was not elevated among those with other CVDs. Males with CAD and females with CAD or any CVD had been hospitalized significantly more often with depression compared to reference group. Conclusions. Suicidality among patients with cardiovascular diseases has been suggested to associate with depression. Psychiatric consultation is highly recommended in clinical practice for cardiac patients with depression or alcohol-related disorders.